A Study On The Effectiveness Of Ecological Civilization Education In Experimental School Of Chinese Education For Sustainable Development - Zhang, Jing; Ye, Yan (Scholar: Human Sciences, 2019)
Ecological civilization is the wisdom crystallization of China's long-term explorations and researches based on Marxist ecological theory and scientific outlook on development, and the essence is to achieve sustainable development. Since the beginning of the new century, our government has attached great importance to ecological civilization and sustainable development and school education played an important role in this process. With the active promotion of international and domestic related policies and education administrative departments, ecological civilization education deepen its development. This paper focuses on the summary and analysis of the main implementation models and achievements in promoting ecological civilization education by experimental schools of education for sustainable development in the field of elementary education in recent years, aiming at providing reference for further promoting ecological civilization and sustainable development from the perspective of education.